Konseling Behavioral Dengan Teknik Self-Regulated Learning dan Self-Management Untuk Meningkatkan Motivasi Berprestasi Siswa - Kadek Sri Widirahayu; I Ketut Dharsana; Nyoman Dantes (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This research was conducted to (1) test the validity of the contents of the behavioral counseling manual with self-regulated learning and self-management techniques to increase student achievement motivation, (2) test the practicality of the contents of the behavioral counseling manual with self-regulated learning and self-management techniques to increase achievement motivation students, and (3) testing the effectiveness of behavioral counseling guidebooks with self-regulated learning and self-management techniques to increase student achievement motivation. This study uses research and development methods using the 4D model by Thiagarajan. This study uses a questionnaire instrument achievement motivation. Evaluation of the contents of the counseling manual was carried out by five experts in the field of counseling guidance. The results of this study (1) the content validity of the behavioral counseling guidebook with self-regulated learning and self-management techniques to increase student achievement motivation in each item is 1 (CVR>0). (2) the practicality of the contents of the behavioral counseling guidebook with self-regulated learning and self-management techniques to increase student achievement motivation in each item is 93.75. (3) the effectiveness of behavioral counseling guidebooks with self-regulated learning and self-management techniques to increase achievement motivation is 72.33.